A Systematic Review and Meta-Analysis of Molecular Characteristics on Colistin Resistance of Acinetobacter baumannii - Ihsan Hakki Ciftci; Elmas Pinar Kahraman Kilbas; Imdat Kilbas (Diagnostics)
Background: This study aimed to determine the molecular epidemiology of colistin-resistant A. baumannii in the last ten years and the frequency of gene regions related to pathogenesis, to compare the methods used to detect genes, and to confirm colistin resistance. Methods: This meta-analysis study was conducted under Preferred Reporting Items for Systematic Reviews and Meta-Analysis Guidelines. In the meta-analysis, research articles published in English and Turkish in electronic databases between January 2012 and November 2023 were examined. International Business Machines (IBM) Statistical Package for the Social Sciences (SPSS) Statistics for Macbook (Version 25.0. Armonk, NY, USA) was used for statistical analysis. The Comprehensive Meta-Analysis (CMA) (Version 3.0. Biostat, NJ, USA) program was used for heterogeneity assessment in the articles included in the meta-analysis. Results: After evaluating the studies according to the elimination criteria, 18 original articles were included. Among colistin-resistant strains, blaOXA-51 positivity was 243 (19.61%), blaOXA-23 was 113 (9.12%), blaOXA-58 was 7 (0.56%), blaOXA-143 was 15 (1.21%), and blaOXA-72 was seen in two (0.16%) strains. The positivity rates of pmrA, pmrB, and pmrC were found to be 22 (1.77%), 26 (2.09%), and 6 (0.48%). The mcr-1 rate was found to be 91 (7.34%), the mcr-2 rate was 78 (6.29%), and the mcr-3 rate was 82 (6.61%). Conclusions: The colistin resistance rate in our study was found to be high. However, only some research articles report and/or investigate more than one resistance gene together. Additionally, it may be challenging to explain colistin resistance solely by expressing resistance genes without discussing accompanying components such as efflux pumps, virulence factors, etc.